Die Suid-Afrikaanse bestuurder: Uitdagings en dilemma - R. Uys (South African Journal of Business Management, 1989)
– The South African manager: Challenges and dilemma The South African working environment is typified by two extremes. On the one hand there is an over-supply of unskilled labour, whilst on the other hand there is a severe shortage of qualified persons which have the applicable experience. In addition white males are mainly used to fill managerial positions. This unavoidably leads to the over-utilization of white males within the management sphere. Not only do they try to cover the whole managerial spectrum, but they also execute the majority of specialist activities. The inevitable result is total work dedication mainly to compensate for the lack of the correct training and experience. This necessarily leads to the neglect of spouse and family and a superficializing of religion, culture, and personal life. To determine to what extend this negative situation actually exists in South Africa and what need to be done to rectify it, country-wide research was undertaken and the findings are recorded in this article.
Keywords: 650